An international investigation into O red blood cell unit administration in hospitals: the GRoup O Utilization Patterns (GROUP) study. Issue 10 (25th August 2017) - Zeller, Michelle P.; Barty, Rebecca; Aandahl, Astrid; Apelseth, Torunn O.; Callum, Jeannie; Dunbar, Nancy M.; Elahie, Allahna; Garritsen, Henk; Hancock, Helen; Kutner, José Mauro; Manukian, Belinda; Mizuta, Shuichi; et al.
Abstract : BACKGROUND: Transfusion of group O blood to non‐O recipients, or transfusion of D– blood to D+ recipients, can result in shortages of group O or D– blood, respectively. This study investigated RBC utilization patterns at hospitals around the world and explored the context and policies that guide ABO blood group and D type selection practices. STUDY DESIGN AND METHODS: This was a retrospective study on transfusion data from the 2013 calendar year. This study included a survey component that asked about hospital RBC selection and transfusion practices and a data collection component where participants submitted information on RBC unit disposition including blood group and D type of unit and recipient. Units administered to recipients of unknown ABO or D group were excluded. RESULTS: Thirty‐eight hospitals in 11 countries responded to the survey, 30 of which provided specific RBC unit disposition data. Overall, 11.1% (21, 235/191, 397) of group O units were transfused to non‐O recipients; 22.6% (8777/38, 911) of group O D– RBC units were transfused to O D+ recipients, and 43.2% (16, 800/38, 911) of group O D– RBC units were transfused to recipients that were not group O D–. Disposition of units and hospital transfusion policy varied within and across hospitals of different sizes, with transfusion of group O D– units to non‐group O D– patients ranging from 0% to 33%. CONCLUSION: A significant proportion of group O and D– RBC units were transfused to compatible, nonidentical recipients, although the frequency of this practice varied across sites.